Legacies of Contention: Revisiting the 2011 Protest Wave. Issue 2 (1st December 2021) - Abdel-Samad, Mounah; Boyle, Michael; Flanigan, Shawn; Garland, Christian; Jefferson, Tony; Jeffery, Bob; Maidhof, Callie; Sotiropoulos, George
Abstract: Ten years ago, a seemingly titanic wave of contention swept the globe. This article reflects on how the impact of a wave of contentious political action that is now a full decade old manifests today. These "legacies of contention"—the historically contingent impact of contentious episodes—can variably re-enforce, undermine, or depart substantially from the original focus of a given contentious episode, a sign of how difficult it can be to extrapolate from the causal impact of contentious politics in the near-run. Herein we discuss the fates of some of the 2011 contentious episodes, including Syria, Greece, Israel, England, and the United States.